Proton beam therapy for olfactory neuroblastoma. Issue 3 (March 2017) - Nakamura, Naoki; Zenda, Sadamoto; Tahara, Makoto; Okano, Susumu; Hayashi, Ryuichi; Hojo, Hidehiro; Hotta, Kenji; Kito, Satoe; Motegi, Atsushi; Arahira, Satoko; Tachibana, Hidenobu; Akimoto, Tetsuo
Abstract: Purpose: To clarify the efficacy and feasibility of proton beam therapy (PBT) for olfactory neuroblastoma (ONB). Methods and materials: We retrospectively reviewed 42 consecutive patients who received PBT with curative intent for ONB at National Cancer Center Hospital East from November 1999 to March 2012. Results: Five patients (12%) had Kadish A disease, nine (21%) had Kadish B, and twenty-eight (67%) had Kadish C. All patients except one received a total dose of 65 Gy (relative biological effectiveness: RBE) in 26 fractions. Twenty-four patients (57%) received induction and/or concurrent chemotherapy. The median follow-up for all eligible patients was 69 months (7–186). The 5-year overall survival (OS) and progression-free survival (PFS) rates were 100% and 80% for Kadish A, 86 and 65% for Kadish B, and 76% and 39% for Kadish C, respectively. The sites of the first progression were local in six patients (30%), regional in eight (40%), distant in two (10%), local and regional in two (10%), and local and distant in two (10%). Late adverse events of grade 3–4 were seen in six patients (ipsilateral visual impairment, 3; bilateral visual impairment, 1; liquorrhea, 1; cataract, 1). Conclusion: PBT was a safe and effective modality for ONB.